Les représentations du risque avalancheux chez les pratiquants d’activités récréatives hivernales du Massif vosgien - Florie Giacona; Frédérick Guyon (Revue de Géographie Alpine)
Whereas numerous studies questioned the risk concept in France, few so far focused on medium-high altitude avalanches, even though those occur on a regular basis. This article studies how winter outdoor activities practitioners apprehend avalanche risk in the Vosges Mountains (north-east France). Our survey demonstrates that their perception of both the mountain environment and avalanche risk is influenced by their culture of sports and mountains in general. Analysis shows a diversity of knowledge and perception of the risk. However, a significant number of practitioners (including hikers, skiers or mountaineers) seem to have no culture at all of avalanche risk, which is preventing them from realizing they are exposed. As a consequence, one can say that this lack of feeling vulnerable has led to an absence of mental construction of avalanche risk in the Vosges Mountains.